1990
DOI: 10.1288/00005537-199004000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The functional result of mandibular reconstruction

Abstract: A study was performed to determine if patients who underwent mandibular reconstruction were functionally rehabilitated. Five parameters were evaluated: deglutition, mastication, cosmesis, diet, and the use of dentures. Deglutition was not improved in patients who had mandibular continuity restored. Problems with deglutition were related to soft tissue resection. Mastication was poorer in the reconstructed group due to scarring, loss of the muscles of mastication, and inhibition of compensatory mandibular motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 48 publications
1
53
1
2
Order By: Relevance
“…This was consistent with the results obtained in one other study, but was higher than those of other reports which ranged between 0 and 12%. 7,9,10,20 There is no general agreement that endosseous implants should fail to a higher degree due to irradiation. 33 Radiation exceeding 50 Gy can cause destruction of capillaries, proliferative endarteritis, damage to osteoprogenitor cells, and overall reduced neovascularity, which can impair the process of osseointegration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with the results obtained in one other study, but was higher than those of other reports which ranged between 0 and 12%. 7,9,10,20 There is no general agreement that endosseous implants should fail to a higher degree due to irradiation. 33 Radiation exceeding 50 Gy can cause destruction of capillaries, proliferative endarteritis, damage to osteoprogenitor cells, and overall reduced neovascularity, which can impair the process of osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…4 Research in this field has mainly focused on the survival rate of the flap and postoperative complications. [5][6][7][8][9][10] The ultimate goal of such a surgical reconstruction should be functional dental prosthetic rehabilitation, placing dental implants in the reconstructed area may overcome problems related to dental rehabilitation with removable prostheses. [11][12][13][14] Fibular bone presents favorable conditions for implant placement, and subsequent implant supported prosthetic rehabilitation, due to its diameter and the good quality of its cortical bone.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is more likely to be achieved by the use of carefully planned autogenous bone grafts and the implantation of reconstructed sites to allow the provision of an implant supported fixed prosthesis. 2,3 The contribution of imaging and digitised data to mandibular reconstruction and implant stabilised occlusal rehabilitation: a case report † …”
Section: Clinical Casementioning
confidence: 99%
“…Many reconstructions restore mandibular continuity and provide good cosmetic results, but fail to achieve a functional result. Study have shown that mucosal resection is the factor that has the greatest impact on the resultant postoperative oral function [10]. Using stringent criteria for success, the majority of oral cancer appeared to benefit little from aggressive reconstruction of the mandible [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Study have shown that mucosal resection is the factor that has the greatest impact on the resultant postoperative oral function [10]. Using stringent criteria for success, the majority of oral cancer appeared to benefit little from aggressive reconstruction of the mandible [10,11]. Patients with carcinoma of the oral cavity are usually heavy smokers and are predisposed to atherosclerotic disease and other co-morbid conditions, and in these patients micro-vascular surgery may be an ill advice.…”
Section: Introductionmentioning
confidence: 99%